Problems experienced by professional nurses caring for HIV/AIDS patients in public hospitals of Polokwane Municipality, Limpopo Province - Mametja, Victoria Lesetja (My University, 2013)
Background: The growing human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) pandemic continues to make a serious impact on all countries throughout the world. Globally, countries have responded to the HIV/AIDS pandemic by investing millions of dollars to help fight the disease, but the impact of HIV/AIDS is even greater in developing countries of Sub-Saharan Africa, including South Africa. Aims: The aims of this study were to describe the perceived problems experienced by professional nurses who provide health care to patients living with HIV/AIDS in public hospitals of Polokwane municipality, Limpopo Province and to identify guidelines to support these professional nurses. Study method: A qualitative, descriptive and contextual method was used in this study. Semi-structured, one-to-one interviews were conducted with professional nurses who participated voluntarily in the study. Tesch’s open-coding method was used for data analysis. Results: Professional nurses who provided care to people living with HIV/AIDS at Polokwane Hospital expressed feelings of frustrations and work overload, treatment delay, lack of knowledge on HIV/AIDS, lack of support systems, poor prognosis and patients presenting with confusion and mental disturbances. Conclusion and recommendations: Despite the fact that the professional nurses expressed negative experiences as they carried out their daily activities, and they still continued rendering care to HIV/AIDS patients, notwithstanding the obstacles they encountered. Recommendations were made with regard to nursing practice and nursing education, staff support by vii management, education and counselling for relatives, reaching out to the relatives and community, and further research.
Thesis (M. Cur.)-- University of Limpopo, 2013
Keywords: Professional nurses; Health care; HIV/AIDS; Nurses -- Attitudes; Nursing -- South Africa -- Limpopo; Nurse and patient; Aids (Disease) -- Patients -- Care